Emerging Strategies in Drug Development and Clinical Care in the Era of Personalized and Precision Medicine - Cristina Manuela Drăgoi; Alina Crenguța Nicolae; Ion-Bogdan Dumitrescu (MDPI AG, 2024)
In the ever-changing landscape of modern medicine, we face an important moment where the interplay of disease, drugs, and patients defines a new paradigm [...]